Desempenho silvicultural e qualidade da madeira de clones de Eucalyptus em sistemas de integração lavoura pecuária floresta - Matias, Stella Vilas Boas Gonçalves (2015)
The aim of this study was to evaluate the silvicultural performance of three Eucalyptus clones in different arrangements of plant spacing on Integration Crop Farming Forest system, 72 months after its implementation. Three clones and three spacing were studied on silvicultural performance and also possible defects related with the performance of the forest and wood end uses. This work was developed with three chapters. The first chapter contains a bibliographic review of concepts of system iLPF, on the clones implanted in the system, and some important factors related to silvicultural performance, planting spacing and the parameters used to assess wood quality. In the second chapter, it was evaluated the influence of different clones of eucalyptus and arrangements and on their production, to 72 months after implantation in iLPF system. The design was a randomized block in a split plot design with three replicates. In the plots, GG100, I144 and VM58 clones were planted; in the subplots, eucalyptus arrangements were distributed in double lines: (3 x 2) + 20m, (2 x 2) + 9m and simple: 9 x 2m. The variables such as diameter at breast height (DBH), total plant height (H) basal area per plant and per hectare, volume per plant and per hectare were assessed. Data analysis showed that the smaller diameter at breast height values, sectional area and volume per plant were found in the spacing (2x2) + 9m. And this same spacing the largest basal area and volume per hectare were found. GG100 clone showed the smallest sectional area, basal area and volume per plant values. But VM58 clone had the lowest height. And the highlight was I144 clone that had the highest volume per hectare. In the third chapter, the tapering of cubed trees was evaluated, as waste and concomitant deformation cracks found in the logs. The design for the form factor, thinning and cracks was the randomized blocks in a split plot design with three replicates. In the plots were distributed eucalyptus arrangements in double lines: (3 x 2) + 20m, (2 x 2) + 9m and simple: 9 x 2m, and in the subplots, GG100, I144 and VM58 clones were planted. For Longitudinal Residual Deformation (DRL) it was used randomized blocks in a split plot design with three replicates and two positions on the line and planting spacing. Data analysis showed that factors that best corrected cylinder volume to solid volume was 0.49 to GG100 clone; 0.47 for I144 clone and 0.39 for VM 58 clone and that the DRL values were affected only by the panel positions and the line spacing. Regarding cracks, interaction between clones and spacing were significant for the length of the top crack, and the thickness of the top crack, which probably indicates that they vary according to the arrangement and the genetic material.